Bentuk-Bentuk Kerjasama Dalam Kegiatan Bisnis Ditinjau Dari Perspektif Hukum Bisnis (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to find out how the legal rules regarding cooperation agreements in business activities are viewed from a business law perspective and what forms of cooperation in trade activities can be carried out by company management. By using normative juridical research methods, it is concluded: 1. The legal rules regarding cooperation agreements in business activities are reviewed from the perspective of business law, referring to Civil law, especially Article 1313 of the Civil Code, which states that